Modelagem geológica do Aquífero Alter do Chão utilizando perfis geofísicos de poços - Souza, Bruno Silva de (Brasil, 2023)
The Groundwater is a resource of high economic, strategic, and social value, whose sustainable use requires extensive knowledge. The Alter do Chão Aquifer, source of groundwater in Manaus (AM), represents the saturated portion of the Alter do Chão formation, being the main water reservoir of the Amazon Basin and one of the most important aquifers of Brazil. However, information about the aquifer do not show clear spatial connotations when treated in 3 dimensions, so it is necessary subsurface data and spatial representation methods - such as the generation of 3D block models from geological modeling – to provide more data from the aquifer characteristics. In this sense, to acquire data with greater viability, the well logging is an alternative which estimates diferente layers resulted from interpretation of profiles that quantify the physical characteristics of the rocks. In this study, fifteen wells with Gamma Ray (RG), Spontaneous Potential (SP) and Resistivity (RE) profiles were used, interpreted from sandstone and clay lithologies collected in gutter samples. For the geological modeling, the Datamine Studio RM software was used, in which the interpreted data of the profiles are inserted in a database, and after validations and statistical treatments they are used for the construction of wireframes, prototype delimitation and blocking. The generated model represents 26.96 km3 of rocks (77.6% sandstone and 22.4% claystone) and is composed by 48 blocks in the X direction, 40 in the Y direction and 66 in the Z direction, totaling 126,720 parent cells, each with dimensions of 250 x 250 x 5 m, considered to have the best adherence for structuring the unit's lenses. The profiles visualization and the definition of 3 lithological zones (called superior, intermediate, and inferior) was considered na accurate method in the evaluation of the Alter do Chão aquifer boundaries, being compatible with the results obtained by 2D mappings and numerical modeling. With regard to integrity, the insertion of structural data, the use of more wells, in a grid with greater regularity, and the availability of hardware with greater processing capacity for microlayer modeling, also tend to increasingly increase the degree of confidence of 3D model.